Spatial Development of the University of Maribor - Lobnik, Uroš; Gabrijelčič, Peter (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
This chapter examines the fifty-year spatial development of the University of Maribor within the context of social, political, and urban planning dynamics. In its first twenty-five years of operation, despite significant spatial and infrastructural constraints, the university successfully integrated its activities into the urban fabric of Maribor, establishing an extensive network of facilities along the left bank of the Drava River. Over the past decades, the expansion of university infrastructure has progressed dynamically, resulting in the establishment of more than twenty units across eight municipalities, continuously shaped through interactions among institutional demands, urban planning strategies, and broader socio-economic trends. Open and long-term spatial planning, coupled with adaptability, remain core principles underpinning the university’s spatial development, which today plays a key role in the sustainable transformation of regional areas and in reinforcing the urban identity of towns and settlements.